Experimental Study on FRP-to-Concrete Bonded Joints with FRP Sheet Anchor System - Weiwen Li; Wei Liu; Xu Yang; Feng Xing (Advances in Materials Science and Engineering)
Fiber-reinforced polymer (FRP) has been widely used for retrofitting and strengthening concrete structures over the past two decades. Because concrete members retrofitted by externally bonded FRP sheets can fail prematurely in debonding because of the fracture between FRP and concrete, FRP tensile strength cannot be fully utilized in engineering practices. Numerous useful investigations have been conducted to develop effective anchor systems to restrict FRP debonding. Thus, an FRP sheet-anchor system was developed and observed to be one of the most effective and convenient anchor systems. The FRP sheet-anchor system is applied to reinforced concrete beams strengthened with U-wrapping and side-bonded FRP configurations in few design guidelines. However, only a few investigations have focused on the failure mechanism of the FRP sheet-anchor system in the existing literature. Therefore, the main objective of this study is analyzing the effect of the carbon FRP (CFRP) sheet-anchor system on the bonding behavior of the CFRP-concrete interface, particularly the effect of the width and stiffness of the CFRP sheet-anchor system. In addition, the anchor-strengthened stage is defined by the load-slip response, which is different from that of specimens without the CFRP sheet-anchor system. Based on the experimental results, three linear stage models of the bond-slip constitutive relationship are proposed in this study.